A Comparative Legal Analysis of the Right of Association in Trade Unions in Ukraine and the Countries of the European Union - Kaplin, Serhii (Teisė, 2021)
The constitutional regulation of the status of trade unions in Ukraine has incorporated all international standards and, in comparison with some constitutions of the states of the European Union, contains detailed regulation of this right. The effective functioning of the institution of trade unions can have a significant impact not only on the protection of the social and economic rights of workers in the process of interaction with employers, but also influence the public authorities in order to optimize the implementation of social policy at the national level and reduce social tension.
Keywords: trade union; constitutional law; the European Union; the Constitution of Ukraine